Elements of space technology for aerospace engineers - Meyer, Rudolph X.
Written for an introductory course in space technology. This book is for senior or graduate level aerospace engineering students and professional engineers seeking an understanding of the aerospace aspects of space systems. It focuses on the primary physics and engineering fundamentals necessary to understand and design space based systems.